Training of learning video making on the equivalency programme at SPNF SKB Boto, West Sumbawa Regency - Hasanuddin Hasanuddin; Puryadi Puryadi; Agus Jayadi; Hari Asgar; Amrussalam Amrussalam; Junaidi Efendi; Amirul Hilmi; Andi Maria Ulfa; Sulaimansyah Sulaimansyah; Sastrowijoyo Sastrowijoyo; Rahmawati Rahmawati; Miranti Nur Wulandari (Universitas Muhammadiyah Magelang, 2022)
The program aims to increase the insight and skills in the field of information and communication technology for tutors of the SPNF SKB Boto Equivalence Program, West Sumbawa Regency. This is expected to improve the quality of teaching and learning through the convenience of students in understanding the teaching material provided. The method of this training activity is carried out by the lecture method and independent practice in three stages, namely: delivery of basic material, training and practice demonstrations and evaluation. The result of this training video learning is increasing the understanding and insight of the participants in making learning videos and to be able to practice making simple learning videos so that they can support online learning in the SPNF SKB Boto environment, West Sumbawa Regency.